Importance and Relevance of Phytochemicals Present in Galenia africana - Dario Heredia; Ivan Green; Jeremy Klaasen; Farzana Rahiman (Scientifica)
Many people in developing countries rely primarily on medicinal plants as their main source of healthcare, particularly for the treatment of skin infections. Despite the widespread use of medicinal plants, there is a lack of literature describing the relevance and risks of exposure of the phytochemicals present. Galenia africana has been used traditionally in the form of pastes, decoctions, and lotions to treat wounds and other skin-related ailments. This is a report on the phytochemical composition of G. africana and a review on the pharmacological importance and relevance of these phytochemicals. The major groups of phytochemicals identified in G. africana extracts were aliphatics, aliphatic triterpenoids, fatty acids, flavonoids, and phenolic and tocopherol compounds. These have been found to exhibit medicinal properties, thus highlighting the need to assess the safety of G. africana for topical application. The information related to the safety of the various compounds could indicate the potential risks related to accidental intake of the extract upon topical product applications. This report concludes that the quantities of the phytochemicals present in G. africana should not cause undue risk to human health, which provides comfort to pursue future work on using and developing G. africana as a therapeutic agent.